Longitudinal examination of pancreatic β‐cell function in Japanese individuals - Fujikawa, Rumi (J Diabetes Investig, 2019)
AIMS/INTRODUCTION: We carried out a retrospective, longitudinal analysis of β‐cell function between a diabetes mellitus group, including those that progressed to diabetes mellitus during the follow‐up period, and a diabetic type with glycated hemoglobin (HbA1c) <6.5 group, including those that progressed to a diabetic type during the follow‐up period. β‐Cell function was assessed using homeostasis model of assessment of β‐cell function. MATERIALS AND METHODS: The relationship between the duration of diabetes mellitus or the diabetic type and pancreatic β‐cell function was compared between the diabetes mellitus group (1,817) and diabetic type with HbA1c <6.5 group (1,843) using results from an oral glucose tolerance test. Linear mixed effects models were used to analyze repeated measurements of oral glucose tolerance tests. RESULTS: The slope of the regression line of β‐cell function for the duration of the diabetes mellitus group was −2.2%/year before the diagnosis. The slope differed after the diagnosis, and the difference was 1.3. The slope of the diabetic type group was −1.2%/year, and no significant difference was observed in the slope before and after the diagnosis. β‐Cell function at the onset was 54.3% in the diabetic type group and 40.6% in the diabetes mellitus group, and the slope of the regression line was significantly higher in the diabetes mellitus group. We divided the diabetes mellitus and diabetic type with HbA1c <6.5 groups into obese and non‐obese participants. β‐Cell function declined more with obesity. CONCLUSIONS: Subsequent declines in β‐cell function were faster in the diabetes mellitus group than that in the diabetic type with HbA1c <6.5 group, and increased with obesity.